2010
DOI: 10.1002/glia.20998
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein‐3 regulates lysosomal function in cultured astrocytes under both normal and oxidative conditions

Abstract: Cellular zinc plays a key role in lysosomal change and cell death in neurons and astrocytes under oxidative stress. Here, using astrocytes lacking metallothionein-3 (MT3), a potential source of labile zinc in the brain, we studied the role of MT3 in oxidative stress responses. H(2)O(2) induced a large increase in labile zinc in wild-type (WT) astrocytes, but stimulated only a modest rise in MT3-null astrocytes. In addition, H(2)O(2)-induced lysosomal membrane permeabilization (LMP) and cell death were comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 50 publications
(69 reference statements)
6
51
0
Order By: Relevance
“…Further, MT III can act as both an acceptor and a donor of zinc, and thus changes in MT III expression could have different effects depending on the cellular environment and redox state within neurons. Knockdown of MT III in astrocytes has also been shown to lead to a decrease in the degradative capacity of lysosomes (Lee et al, 2010), consistent with the reduced autophagy observed during AD. However, the lack of MT III also corresponds with decreased oxidant-induced zinc release, revealing the need for further studies to fully understand the role of MT III and its association with zinc in autophagic dysfunction.…”
Section: Mt III and Adsupporting
confidence: 54%
“…Further, MT III can act as both an acceptor and a donor of zinc, and thus changes in MT III expression could have different effects depending on the cellular environment and redox state within neurons. Knockdown of MT III in astrocytes has also been shown to lead to a decrease in the degradative capacity of lysosomes (Lee et al, 2010), consistent with the reduced autophagy observed during AD. However, the lack of MT III also corresponds with decreased oxidant-induced zinc release, revealing the need for further studies to fully understand the role of MT III and its association with zinc in autophagic dysfunction.…”
Section: Mt III and Adsupporting
confidence: 54%
“…7C). The smeared bands for Lamp1 are indicative of increased Lamp1 glycosylation (Lee et al, 2010). All changes were absent in the double transgenic mice [AN(+/+)].…”
Section: Resultsmentioning
confidence: 99%
“…Although there are examples of zinc's effect on autophagy in bacteria and yeast [168], it is not as clear how these can be translated to mammals. Zn mediates tamoxifen-induced autophagy in breast cancer cells [169], hippocampal neurons [170], retinal cells [167], and in astrocytes via increases in oxidative stress and induction of lysosomal membrane permeabilization [171]. The newer studies have used animals deficient in metallothionein to study the changes and importance of zinc.…”
Section: Zinc Apoptosis and Cancermentioning
confidence: 99%